2021
DOI: 10.21837/pm.v19i15.929
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Community on the Conservation of Heritage Buildings in George Town, Penang

Abstract: Having been gazetted as a World Heritage Site, George Town is known to have many heritage buildings that are more than a hundred years old. However, not all heritage buildings in George Town have appropriately been conserved by the local community, especially the owner and the tenant. This ignorance has caused severe issues of heritage buildings being neglected by the owner and the public. A stud has been carried out on the awareness of the local community in preserving historical buildings within George Town … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…Heritage buildings refer to buildings or structures that have historical, cultural, or architectural significance and are recognized for their value in preserving a community's identity and heritage [5]. These buildings may have been constructed in a specific architectural style or may have played a key role in the history of a particular region or community.…”
Section: Classification Of Heritage Buildingsmentioning
confidence: 99%
“…Heritage buildings refer to buildings or structures that have historical, cultural, or architectural significance and are recognized for their value in preserving a community's identity and heritage [5]. These buildings may have been constructed in a specific architectural style or may have played a key role in the history of a particular region or community.…”
Section: Classification Of Heritage Buildingsmentioning
confidence: 99%
“…The level of community awareness will affect the local community's involvement in heritage conservation (Halim& Tambi, 2021). Public awareness on the extent of the values of heritage is very important in the effort to conserve and preserve cultural heritage.…”
Section: Planning Malaysia Journal Of the Malaysia Institute Ofmentioning
confidence: 99%
“…However, the forces of urbanization often encroach upon this identity, necessitating a closer examination of the impacts on its cultural and historical essence. Halim & Tambi (2021) states that ccommunity involvement and public awareness play pivotal roles in the preservation of historic building identity. Engaging local communities fosters a sense of ownership and responsibility, enabling a collective effort to preserve the heritage Studies have shown that rapid urbanization often leads to increased pressure on urban spaces, resulting in alterations and encroachments on historic buildings The growth of cities and subsequent changes in the built environment can cause a disconnect between the historic context and the present urban landscape.…”
Section: Literature Reviewmentioning
confidence: 99%